(3JdNjU GdLGeY GdcHjQs - (3eMeO Hf YHGO Hf edc OGO Hf GdMSf Hf OGhO, CHh YHO Gddg GdNdGWj, UOQ GdOjf , J (B652 (3g` s; (3CHh YHO Gddg eMeO Hf GdMSf Hf aQbO, GdTjHGfj,J (B189 (3g` s ((3Ydi Hf Ndjd Hf jhSa GdWQGHdSi s)
(3ChdgG (B:s
(3hGdJMGda ai Gdcd cGf MPGQ ahJ GdfXQ HJChjd CaQGO GdHYV s
(3BNQgG (B:s
(3hGdZhU ai Md CTcGdgbO Je HYhf Gddg Gdedc GdhgGH s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80s
Keywords: (3Gdabg GdMfajs